2009
DOI: 10.1063/1.3216918
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of surface plasma waves by an electron beam in a magnetized dusty plasma

Abstract: An electron beam drives surface plasma waves to instability on a vacuum magnetized dusty plasma interface and in a magnetized dusty plasma cylinder via Cerenkov and fast cyclotron interaction. The dispersion relation of a surface plasma wave has been derived and it has been shown that the phase velocity of waves increases with increase in relative density δ(=ni0/ne0)), where ni0 is the ion plasma density and ne0 is the electron plasma density of negatively charged dust grains. The frequency and the growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Following Prakash and Sharma, we consider a plasma–vacuum interface at x =0. The plasma occupies half of the space x <0 with permittivity ε, given as ε=1ωpe2ω02, where ωpe1.61em=()4πnpe2me1false/21.61em is the electron plasma frequency, n p is the plasma density, m e is the mass of electron, and e is the electronic charge.…”
Section: Modelmentioning
confidence: 99%
“…Following Prakash and Sharma, we consider a plasma–vacuum interface at x =0. The plasma occupies half of the space x <0 with permittivity ε, given as ε=1ωpe2ω02, where ωpe1.61em=()4πnpe2me1false/21.61em is the electron plasma frequency, n p is the plasma density, m e is the mass of electron, and e is the electronic charge.…”
Section: Modelmentioning
confidence: 99%
“…In laboratory dusty plasma discharges, new effects are introduced by the dust charge fluctuation dynamics, dust-dust interactions, dust grain rotation, and the plasma boundary, which are unique for dusty plasma (Shukla & Mamun, 2002;Shukla & Eliasson, 2009). Theoretically, dust effects have been investigated by extending the usual two-fluid treatment of plasmas with the addition of a third component -the dust (Sharma & Sugawa, 1999;Sharma & Srivastava, 2001;Lee & Jung, 2005;Sharma & Walia, 2008;Prakash & Sharma, 2009;Gupta et al, 2010). Ostrikov et al (1999) have studied the effect of dust on surface wave produced microwave discharges and found that the dust can lead to a modification of the electromagnetic field structure in the discharge by shifting the originally excited operating mode out of resonance.…”
Section: Introductionmentioning
confidence: 98%
“…The properties of SPW strongly depend on the properties of the interface along which it propagates. It can be excited by an electron beam (Liu & Tripathi, 2000;Prakash & Sharma, 2009;Girka et al, 2011a;2011b), by an ion beam (Girka et al, 2011a;2011b), by attenuated total reflection (ATR) configuration (Kretschmann & Raether, 1968;Kretschmann, 1971;Fink & Schneider, 1975), by ripples of suitable wave number over the metallic interface (Liu & Tripathi, 2000), by light via prism coupling (Chen et al, 2011), or by laser (Anisimov et al, 1988;Parashar et al, 1998;Bouhelier et al, 2007). The interaction of laser beam with plasma eigenmodes is also an important area of research (Ghorbanalilu, 2012;Verma & Sharma, 2011;Sharma et al, 2010;Saini & Gill, 2006;Anderson et al, 2005;Paknezhad & Dorranian, 2011) in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] These waves play a crucial role in laser ablation, 8 high sensitivity sensors, 9 and are being explored for their potential in subwavelength optics, magneto-optic data storage, microscopy, and solar cells. [10][11][12][13] The problem of transferring energy from a beam of particles into electromagnetic wave energy has been given considerable attention in various fields of physics.…”
Section: Introductionmentioning
confidence: 99%